A cross cultural definitions of orphanages - Azlini, Chik; Siti Hajar, Abdul Rauf; Lukman@Zawawi, Mohamad (2020)
Orphans are children with one or both deceased parents in need of care and protection. while, on behalf of the government, the task of running an orphanage as well as providing physical and social facilities is under Social jurisdiction. Therefore, this article aims to discuss cultural definitions of orphanages using the findings of previous studies. The findings show that there is a difference in the definition of orphanage.